A wizard of Earthsea - Le Guin, Ursula K., 1929-; Robbins, Ruth (New York : Bantam Books, 2004)
A boy grows to manhood while attempting to subdue the evil he unleashed on the world as an apprenctice to the Master Wizard.
6.1
5-8.
Keywords: Magic -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Fiction; Wizards -- Fiction; Fantastic fiction